G19(P) Standardisation of hip surveillance in cerebral palsy: a new approach. (May 2019) - Kurup, B; Riley, G; Imtiaz, R; Nicholson, C
Abstract : Background: Hip displacement is second most common musculoskeletal deformity in children with cerebral palsy (CP). Retrospective review of notes over a period of one year in 2010 in children with CP showed that they are not being monitored regularly in terms of hip displacement. A quarter had hip dislocations requiring surgeries. Originally our Trust protocol for pelvic x-ray requests were to take both AP and frog legged views in CP children. Reports were provided by different radiologists and there were no standardizations. The radiology reports did not universally address Migration percentage (MP) which is the percentage of femoral head outside the acetabulum. This is an important index for hip displacement monitoring. Following the review, a protocol for undertaking pelvic x-rays in CP children, which include a single X-ray in AP view, to calculate MP was identified. For accurate measurement of MP, standardisation of positioning of patient whilst taking x-ray is crucial. Unrecognised hip flexion contracture creats lordotic pelvis which is corrected by raising legs on foam pads/pillows, to flatten lumbar spine. Femoral ante -version is corrected by positioning legs with patella facing upwards. Aim: To establish a standardized hip surveillance programme (pathway and guideline) for early identification of hip displacement in CP children, for monitoring displacement progression and for early referral to Orthopaedics. Method: Several meetings were undertaken with paediatricians, physiotherapists, radiologists, and advanced practitioners in radiology to achieve standardization of requesting, positioning and reporting of x-rays. One paediatric Radiologist took the lead in reporting on all Pelvic X-rays. Training day for positioning was organised for advanced practitioners where they positioned five patients with varying degrees of GMFCS, under supervision. Pelvis X-ray requests were standardized to include diagnosis (Cerebral palsy/spasticity), GMFCS, and hip surveillance. Results: We have an established hip surveillance programme from October 2015. This enabled us in identifying who can be monitored locally and who needs referral to Orthopaedics. Subsequent audit has shown marked improvement. We are fully compliant with NICE guidelines in terms of hip surveillance. All patients were appropriately referred to Orthopaedics. Hip dislocations improved from 25% to nil.